2010
DOI: 10.1007/s10546-010-9557-1
|View full text |Cite
|
Sign up to set email alerts
|

General Characteristics of the Atmospheric Boundary Layer Over a Flaw Lead Polynya Region in Winter and Spring

Abstract: A time series of microwave radiometric profiles over Arctic Canada's Cape Bathurst (70 • N, 124.5 • W) flaw lead polynya region from 1 January to 30 June, 2008 was examined to determine the general characteristics of the atmospheric boundary layer in winter and spring. A surface based or elevated inversion was present on 97% of winter (JanuaryMarch) days, and on 77% of spring (April-June) days. The inversion was the deepest in the first week of March (≈1100 m), and the shallowest in June (≈250 m). The mean tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 31 publications
7
38
0
Order By: Relevance
“…Two different values are applied that are typical for the Arctic BL (Lüpkes et al, 2012b). The first one, 350 m, was, for example, measured over a flaw lead polynya in the Canadian Archipelago by Raddatz et al (2011). The second one, 100 m, is close to often observed values (reported e.g.…”
Section: Box Modelsupporting
confidence: 58%
“…Two different values are applied that are typical for the Arctic BL (Lüpkes et al, 2012b). The first one, 350 m, was, for example, measured over a flaw lead polynya in the Canadian Archipelago by Raddatz et al (2011). The second one, 100 m, is close to often observed values (reported e.g.…”
Section: Box Modelsupporting
confidence: 58%
“…Raddatz et al (2011) found similar temperature inversion frequencies for a Canadian polynya region, whereas Tjernström and Graversen (2009) reported, based on SHEBA, that inversions, either surface-based or elevated, are practically always present in the central Arctic. The spatial distribution of temperature inversions is inhomogeneous and strongly controlled by the surface type, the prevailing large-scale circulation conditions and by coastal topography (Pavelsky et al, 2011;Wetzel and Brummer, 2011;Kilpeläinen et al, 2012).…”
Section: Temperature and Humidity Inversionsmentioning
confidence: 84%
“…Mixing in the stratified interior ocean is related to internal wave energy, which tends to be low under the Arctic Ocean ice cover (Levine et al, 1985). Microstructure measurements conducted during the IPY show that the Arctic Ocean is a quiescent environment with background mixing rates close to molecular levels (Rainville and Winsor, 2008;Fer, 2009). Efficient vertical mixing and upward oceanic heat fluxes occur, however, along the continental rise and over topographic features where the warm boundary current is guided (Sirevaag and Fer, 2009;Fer et al, 2010).…”
Section: Diapycnal Mixing In the Arctic Oceanmentioning
confidence: 99%
“…The hourly IPY-CFL MWR temperatures and water vapour profiles have been used to characterize and link the winter through early summer atmospheric boundary layer over Amundsen Gulf to the sea-ice cover (Raddatz, Asplin, Candlish, & Barber, 2011;. The addition of the late summer and fall profiles from ArcticNet2009 to the IPY-CFL time series created a composite year of hourly water vapour profiles which have been used to determine the annual cycle of monthly median precipitable water (PW), and the maximum monthly PW resulting from water vapour intrusions over the western maritime Arctic (Raddatz, Galley, Candlish, Asplin, & Barber, 2012).…”
Section: Introductionmentioning
confidence: 99%